A novel approach integrating FANP and MOMILP for the collection centre location problem in closed-loop supply chain - Yang, Chuanrui; Chen, Xiaohui (International journal of sustainable engineering, 2020)
Supply chain network design plays a crucial role in supply chain management. With government support as well as restriction and legislation, the enhancement of environmental awareness, and the drive of economic interest, reverse logistics have been incorporated into the supply chain, forming a closed-loop supply chain. The collection centre, which helps recycle and classify returned products, is a vital hub in closed-loop networks. Regarding the location problem, this study proposes a novel approach that integrates a fuzzy analysis network process and multi-objective mixed-integer linear programming to analyse qualitative and quantitative factors: social, political, and environmental factors, including costs, emissions, and responsiveness. Hence, an ε-constraint method is applied to examine the proposed framework. Finally, uncertain scenarios and different scale problems are discussed. Orthogonal experiments provide a sufficient basis for decision-making.